Rezension der Deutschsprachigen Wikisource - Susanne Haaf (RIDE, 2018)
The German Wikisource project evolved from a multilingual Wikimedia venture for the digitization of historical text sources. As a sub-project of the Wikimedia Foundation it is substantially based on the non-profit work of voluntarily engaged people. The objective is to digitize German, mostly historical works according to high-standard guidelines and to provide these texts to the public under free licenses. At the moment, the German Wikisource counts 120 active contributors who have digitized about 39,416 works manually or semi-automatically comprising more than 400,000 sub-pages in total. Apart from the the amount of digitized texts, major achievements of the project are the focus on text transcription quality, elaborate documentation and catering to the community of collaborators. In spite of the project’s own scholarly entitlement, there are limitations though for scholarly (out-of-the-box) reuse and there remain desiderata regarding established standards and best-practises for scholarly text digitization und publication. This, however, doesn’t diminish the fact that here a community of volunteers contributes greatly to the digitization of historical works, something scholars of various disciplines might benefit from as well.